Matching higher education offer with labour market needs till 2020 - the case of Lodzkie region - Lukasz Arendt; Agnieszka Rzenca (European Regional Science Association (ERSA), 2014)
Transformation to post-industrial or knowledge-based economies causes changes in the structure of labour markets with growing demand on highly-qualified workforce. In XXI century human capital has become one of the most important production factors determining competitiveness and innovativeness of countries and regions. Creation of adequate stock of human capital requires smart investments. Therefore the higher education system, which is supposed to supply people with high-level skills and knowledge, plays crucial role in this process. The paper focuses on the linkage between higher education offer and labour market needs in the regional perspective. The goal of this paper is to analyse the extent to which higher education is able to response to demand-driven changes on the Polish labour market, especially in the Lodzkie region, till 2020. We use the newest employment forecast data to 2020 to present the development patterns of the labour demand in Poland and in the Lodzkie region. The analysis of data seems to confirm, that shifts in the sectoral and occupational structure of employment will follow the path consistent with the hypothesis of the skill-biased technical change. This implies growing demand on skills, and thus growing importance of the ability of higher education system to meet this challenge in coming years. We elaborate on the reforms of the Polish system of higher education that have been introduced since 1990ties. The main focus is put on the two groups of determinants - external, like the Bologna process, and introduction of the European Qualifications Framework, and internal - those, which are related to the specific socio-economic drivers at national and regional level. This analysis takes into account the outcomes of the recent debate, that emphasizes the linkage between higher education and labour market - it is generally acknowledged, that higher education should support labour market by adapting curricula and learning environment to the contemporary needs of the demand-side of this market. To assess this issues, we present unique data collected within primary research study carried out in the Lodzkie region (especially calculations of HRSTE and description of structure of education offer in the field of science and technology). We propose actions and recommendations to cope with the problem of matching higher education outcomes with the labour market needs.
Keywords: I23; I25; J23; J24; 330; labour market; human capital; higher education; education profile; labour demand forecasts